2021
DOI: 10.1002/cdq.12269
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Model of College Students’ Proactive Personality and Career Adaptability

Abstract: College is a key period for students' specialty study and development, and an important stage of career exploration. We examined the relationship between proactive personality, career adaptability, and perceived social support and specialty identity among 610 Chinese college students. The mediating effect of perceived social support was greater than that of specialty identity. Therefore, providing more social support to college students may be more conducive to increasing their career adaptability. The chain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
14
0
5
Order By: Relevance
“…Magában foglalja a változó feladatokhoz való alkalmazkodás képességét, a folyamatos önképzésben való részvételt és a karrier irányának szabályozását (Savickas & Savickas, 2017). A karrier-alkalmazkodóképesség nagyobb fokú felkészültséggel és megküzdési képességgel jár együtt a kiszámítható tanulási feladatok vagy a kiszámíthatatlan problémák vonatkozásában (Hu et al, 2021). A proaktív személyiség összefügg az önkezdeményezéssel, vagyis a proaktív munkavállaló előre látja és képes megelőzni a problémákat.…”
Section: Cikkek Tanulmányokunclassified
“…Magában foglalja a változó feladatokhoz való alkalmazkodás képességét, a folyamatos önképzésben való részvételt és a karrier irányának szabályozását (Savickas & Savickas, 2017). A karrier-alkalmazkodóképesség nagyobb fokú felkészültséggel és megküzdési képességgel jár együtt a kiszámítható tanulási feladatok vagy a kiszámíthatatlan problémák vonatkozásában (Hu et al, 2021). A proaktív személyiség összefügg az önkezdeményezéssel, vagyis a proaktív munkavállaló előre látja és képes megelőzni a problémákat.…”
Section: Cikkek Tanulmányokunclassified
“…In previous studies, career adaptability is positively related to proactive personality ( Guan et al, 2014 ; Taber and Blankemeyer, 2015 ). Some studies show that proactive personality can predict an individual’s career adaptability ( Uy et al, 2015 ; Hu et al, 2021 ). The study by Green and Batool (2017) shows that proactive personality is significantly related to all four adapting responses and supports the proposed significance of proactivity for today’s vocational environment with regard to career adaptability resources and adapting responses.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers think proactive personality is an important psychological resource in the college-to-career transition (e.g., Erdogan and Bauer, 2005 ; Brown et al, 2006 ). Many studies have also identified a positive relationship between proactive personality and career adaptability ( Tolentino et al, 2014 ; Cai et al, 2015 ; Jiang, 2017 ; Hu et al, 2021 ) because it represents an internal motivation and behavioral tendency to spontaneously seek breakthroughs without being constrained by situational resistance. For example, Jiang (2017) finds that Proactive personality (PP) is positively related to career adaptability (CA), and PP has a stronger indirect effect on CA via thriving for less proactive workers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding CA, past studies have focused on general company employees ( AlKhemeiri et al, 2020 ; Omar and Tajudeen, 2020 ; Wang et al, 2021 ), student veterans or veterans ( Ghosh and Fouad, 2018 ; Ghosh et al, 2019 ; Becker et al, 2022 ), college students ( Gregor et al, 2021 ; Hu et al, 2021 ; Kim and Smith, 2021 ), high school students ( Dostanić et al, 2021 ), adolescent groups ( Liang et al, 2020 ; Bacanli and Sarsikoğlu, 2021 ), and working women ( Takawira, 2020 ), and have revealed that the target population is very diverse and represents the importance of research on CA.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, most of these studies focused on students’ parental behaviors, expectations of students, and caring support ( Liang et al, 2020 ; Parola and Marcionetti, 2021 ; Nikander et al, 2022 ). External variables, or students’ internal personality traits and active personality ( Bacanli and Sarsikoğlu, 2021 ; Hu et al, 2021 ; Chang and Liu, 2022 ) have been less frequently explored in terms of MT, SE, and other intrinsic subjective drivers that are at the core of a person’s being from a self-deterministic perspective.…”
Section: Introductionmentioning
confidence: 99%